Evaluasi Stabilitas Breakwater pada Kecamatan Panjang - Kurniawan, Rizqi; Tugiono, Subuh; Wahono, Endro Prasetyo; Zakaria, Ahmad (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2021)
Abstract The coast will be easily damaged due to large waves, causing damage to the area around the coastal area which is densely populated with various activities, namely Pantai Kecamatan Panjang, among others as ports, settlements, industry, trade, tourism and fishing activities. With so many activities, it should be accompanied by development that prioritizes conservation aspects to reduce the impact of environmental degradation. One of the efforts to overcome the impact of its degradation is to make a breakwater. This study aims to assess and study the failure of the protected layer unit at the breakwater on the coast of Kecamatan Panjang, so testing the stability of the protected layer using a physical model was carried out at the Hydraulics Laboratory of the University of Lampung using an experimental method. The results showed that the level of breakwater damage was 0% at 4,47 cm HHWL position with a plan wave height of 4 cm. So, the crushed rock will work well to protect the breakwater. Key words: Breakwater, Armor Units, Physical Model, Stability